Theoretical Principles of Training Future Lawyers to the Professional Activity in the Penitentiary System of Ukraine - Liubov Sitovska (Pedagogical Discourse, 2014)
The article analyzes the basic concepts which characterize preparation of future legal specialists for professional activity in the Ukrainian penitentiary system. Preparation of future legal specialists for professional activity in the Ukrainian penitentiary system is the new trend of higher education in Ukraine. The concept of the «penitentiary system» is the central, fundamental in the conceptual system of preparation of future legal specialists for professional activity in the penitentiary system. Theoretical maintenance of concept «training of future lawyers to the professional activity in the penitentiary system of Ukraine» is specified.